Patient Satisfaction and Quality of Life after Bariatric Surgery among Iraqi Patients - Taqi Mohammed Jwad Taher; Ali Abdul Jabbar Mahdi (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Obesity is a global epidemic associated with significant health and economic burdens. Bariatric surgery has emerged as a highly effective intervention for severe obesity, offering substantial and sustained weight loss, resolution of comorbidities, and improved quality of life (QoL). Materials and Methods: This cross-sectional descriptive study evaluated patient satisfaction and QoL outcomes among 150 patients who underwent bariatric surgery in Al-Zahraa Teaching Hospital and private clinics in Wasit Province, Iraq. Participants completed a structured questionnaire assessing satisfaction with surgical outcomes, QoL metrics, and postoperative challenges. Results: The findings revealed a mean BMI reduction of 15.7 kg. Gastric sleeve surgery was the most common procedure (60%). High satisfaction levels were reported, with 46.7% rating postoperative care as excellent, and 80% recommending surgery to others. QoL metrics demonstrated marked improvements, particularly in physical health (73.3% reporting better outcomes), social life (80% reporting positive changes), and emotional well-being (66.7% experiencing improvements). A strong positive correlation (r = 0.65, p < 0.01) was observed between patient satisfaction and QoL. Despite these positive results, 33.3% of patients reported difficulty adjusting to dietary changes, and 26.7% experienced side effects. Conclusion: This study underscores the transformative impact of bariatric surgery on holistic patient well-being. However, the findings also highlight the importance of individualized care and ongoing follow-up to optimize outcomes and address challenges. Further research exploring long-term outcomes and strategies to enhance patient-centric care is recommended.